Healthcare use during COVID-19 and the effect on psychological distress in patients with chronic cardiopulmonary disorders in the Netherlands: a cross-sectional study. Issue 6 (30th June 2021) - Pouwels, Beau D C; Simons, Sami O; Theunissen, Maurice; Peters, Madelon L; Schoenmaekers, Janna J; Bekkers, Sebastiaan C; van den Beuken-van Everdingen, Marieke H J
Abstract : Objectives: The COVID-19 pandemic caused a massive shift in the focus of healthcare. Such changes could have affected health status and mental health in vulnerable patient groups. We aimed to investigate whether patients with chronic pulmonary and cardiac diseases had experienced high levels of psychological distress during the COVID-19 pandemic in the Netherlands. Design: A cross-sectional study. Setting: COVID-19 pandemic-related changes in healthcare use, health status and psychological distress were investigated among patients with chronic obstructive pulmonary disease (COPD), pulmonary fibrosis (PF) and congestive heart failure (CHF), using an online nationwide survey. Participants: 680 patients completed the survey. COPD was the most often reported diagnosis 334 (49%), followed by congestive heart failure 219 (32%) and PF 44 (7%). There were 79 (12%) patients with primary diagnosis 'other' than chronic cardiopulmonary disease, who also completed this survey. Interventions: Psychological distress was assessed via the DASS-21 score (Depression Anxiety Stress Scale). Moreover, specific worries and anxieties regarding COVID-19 were explored. Results: The frequency of contact with healthcare professionals changed in 52%. Changes in treatment were reported in 52%. Deterioration in health status was self-reported in 39%. Moderate to extremely severe levels of depression, anxiety and stress was observed in 25.8%, 28.5% and 14%, respectively. Over 70% reported specific worries and anxieties, such as about their own health and fear of being alone. Both the deterioration in health status and increased levels of anxiety were significantly (p<0.001, p<0.006) associated with changes in treatment. Exploratory analyses indicated that lack of social support may further increase anxiety. Conclusion: Healthcare use changed during the COVID-19 pandemic in the Netherlands. It was associated with a decrease in health status, and increased psychological stress among patients with chronic cardiopulmonary disorders. Provision of healthcare should be more sensitive to the mental health needs of these patients during subsequent COVID-19 waves.